VALUES CHANGES IN THE POLITICAL SPHERE UNDER THE POST-INDUSTRIAL SOCIETY - Munko , Anna (Theory and Practice of Public Administration, 2020)
The evolution of the basic values of society in the light of the concept of the Third wave of E. Toffler has been analyzed. Their changes in time and key interrelation have been discovered. It will allow to adapt the political sphere of public life to the new requirement of the present.This aspects of the power-political institutions of the Second Wave have been aproved. They were created on the basis of the elementary concept of representation. They were united from many sources and supported by an election machine that distributed them in proportion to the size of the party or mixed, presenting their products as the will of the people.Political trends under the Third Wave have also been explored. On one side political power from the nation-state level can be shifted to the level of the intra-national regions and groups. On other side it can be raiseв to the level of multinational organizations. Accordingly, all this leads to the disintegration of nations into smaller units.The crisis of the values of the Second Wave is an incentive for decentralized government. For the transition period in which Ukraine is still located two phenomena have been determined. There are: deepening of differentiation of society, demasification of mass society and growth rate of change. The population of Ukraine is often guided by the values of traditional society. So, the country has not yet resolved the problems of industrial society.The principles of building a political power in a post-industrial society hav been proposed. There are the principles of minority power; semi-direct democracy (moving from representative dependency to self-representation); level distribution of decisions. The value system of government should be based on the predominance of human values over the state-political ones, that is, the latter should be a reflection of personal values.